Approximate Controllability of Impulsive Neutral Functional Integrodifferential Systems with Nonlocal Conditions - Yasotha, A.; Kanagarajan, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study the approximate controllability of impulsive neutral functional integrodifferential systems with finite delay. The fractional power theory and a-norm are used to discuss the problem so that the obtained results can apply to the systems involving derivatives of spatial variables. By methods of functional analysis and semigroup theory, sufficient conditions of approximate controllability of the impulsive integrodifferential equation are formulated and proved. An example is provided to illustrate the theory.